Factors impacting sustainability of community health worker programming in rural Uganda: a qualitative study - Ashaba, Scholastic; Tumuhimbise, Manasseh; Beebwa, Esther; Oriokot, Francis; Brenner, Jennifer L; Kabakyenga, Jerome (African Health Sciences, 2022)
Background: Despite significant global progress towards decreased child mortality in past decades, maternal and child mortality continues to be high, especially in sub Saharan Africa. Most of these deaths are preventable with known interventions. Community health workers (CHWs) are well-positioned to promote these life-saving interventions; however, sustaining CHW programs remains a challenge. Methods: A sustainability-focused qualitative evaluation, was done between July and August 2018 in 2 rural districts in southwest Uganda. Using semi-structured interview tools, we conducted 6 Focus Group discussions (FGDs) with CHWs and 17 in depth interviews (IDIs) with various district stakeholders to gain insights into factors affecting sustainability of a district-wide maternal, newborn and child health (MNCH)-oriented CHW intervention. Data was managed using NVivo software (version 12) with themes using thematic analysis. Results: Identified factors impacting CHW program sustainability included ‘health system effectiveness’ (availability of supplies, medicines and services and availability of facility health providers), CHW program-related factors’ (CHW selection and training, CHW recognition), ‘community attitudes and beliefs’ and ‘stakeholder engagement’. Conclusion: To sustain CHW programs in rural Uganda and globally, planners, policymakers and funders should maximize community engagement in establishing CHW networks and strengthen accountability, supply chains and linkages with communities and health facilities
Keywords: CHWs programs; Sustainability; Maternal newborn and child health; Uganda